Interactions Between Pulmonary Performance and Movement-Evoked Pain in the Immediate Postsurgical Period: Implications for Perioperative Research and Treatment. Issue 4 (1st June 2008) - Erb, Jason; Orr, Elizabeth; Mercer, Dale C.; Gilron, Ian
Abstract : Background and Objectives: : Previous data suggest that movement-evoked pain is more closely correlated with pulmonary performance than rest pain beyond 24 hours following lower abdominal surgery. Because adverse alterations in lung physiology are initiated intraoperatively and impact upon pulmonary morbidity, this study tests the hypothesis that movement-evoked pain correlates negatively with pulmonary performance in the immediate postoperative period. Methods: : We measured pain at rest and pain evoked by sitting, forced expiration, and coughing as well as peak expiratory flow (PEF), forced expiratory volume in 1 second, and forced vital capacity for the first 3 hours after laparoscopic cholecystectomy in 65 patients. Results: : Immediately after surgery, all pain measures were significantly correlated with PEF with a medium effect size. Also, sitting-evoked pain and cough-evoked pain were significantly more intense than rest pain. Pain intensity improved significantly over the first 3 postoperative hours. Conclusions: : Considering these and previous results, pulmonary function tests such as PEF should be considered for more routine use as functional surrogates of movement-evoked pain in analgesic trials of thoracic and abdominal surgery. Mechanisms of immediate postoperative movement-evoked pain may differ from those in effect at later time points after which tissue inflammation and spinal sensitization develop. Because pain adversely impacts upon postoperative rehabilitation, these results further imply that aggressive treatment of movement-evoked pain could improve the outcome of postoperative rehabilitation measures if both are implemented very early after surgery.